DETERMINATION AND SIMULTANEOUSLY QUANTIFICATION OF FIVE ORGANIC VOLATILE IMPURITIES USING HEAD SPACE GAS CHROMATOGRAPHY IN LEVOCLOPERASTINE FENDIZOATE ACTIVE PHARMACEUTICAL INGREDIENTS AND DOSAGE FORMS - Vidyamani, Uppalapati; RAMACHANDRAN, DITTAKAVI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Organic chemical solvents are generally used during drug material synthesis, excipients, as well as in the drug product formulation. They are not acceptable in the finished product. Hence, the main objective of our work is development and validation of rapid, sensitive, and selective head space gas chromatography (GC-HS) method for the determination of five organic volatile impurities (OVI) (methanol, ethanol, dichloromethane, toluene, and benzene) in Levocloperastine Fendizoate active pharmaceutical ingredient (API) and commercial syrups. Methods: The method was developed using a thermal gradient elution program associated with a column having dimensions are ZB-624, 30 m × 0.53 mm × 3.0 μm with a flow rate of 3.0 mL/min and Nitrogen (N2) as a carrier gas. A flame ionization detector was used as a detector, and its temperature is at 250°C whereas the injector temperature is at 225°C. The total run time is 25.0 min. Results: The newly developed GC-HS method was validated by its specificity and selectivity system precision, and method precision, limit of detection and limit of quantification, linearity, accuracy, robustness, ruggedness, and solution stability as per International Council for Harmonization (ICH). Quantization limits for five impurities were 210 ppm for methanol, 350 ppm for ethanol, 42 ppm for dichloromethane, 62 ppm for toluene, and 0.4 ppm for benzene. Correlation coefficient values of linearity were higher than 0.995 for five OVI. The mean recoveries of five impurities were between 90% and 110%. Conclusion: We found good and accepted results as per ICH guidelines for all validated parameters for five OVI. Thus, the developed GC-HS method was suitable for the separation and quantification of five OVI in Levocloperastine Fendizoate API and commercial syrups at present.